2019
DOI: 10.19175/recom.v9i0.3053
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da qualidade de vida em idosos de um centro de convivência

Abstract: Objetivo: Avaliar a qualidade de vida (QV) em idosos que frequentam um centro de convivência do interior do estado de Mato Grosso do Sul. Método: Foram entrevistados 106 idosos por meio dos instrumentos WHOQoL-BREF e módulo WHOQoL-OLD. Resultados: Apontaram escore total de 62,55 para o WHOQoL-BREF e de 66,06 para o WHOQoL-OLD. O domínio e a faceta com maiores escores foram "Relações sociais" (67,22) e "Funcionamento do sensório" (70,87), respectivamente. Já o domínio e a faceta com os piores escores de satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
2
0
0
1
Order By: Relevance
“…In the current study, higher mean scores were observed for the domain of social relationships, similar to studies conducted among older people in the community in Brazil 31 , 34 and Greece. 35 A varying result was shown in a survey in the Netherlands among people aged ≥ 50 years, in which this domain had the lowest QoL scores.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the current study, higher mean scores were observed for the domain of social relationships, similar to studies conducted among older people in the community in Brazil 31 , 34 and Greece. 35 A varying result was shown in a survey in the Netherlands among people aged ≥ 50 years, in which this domain had the lowest QoL scores.…”
Section: Discussionsupporting
confidence: 89%
“…The highest average scores in death and dying, verified in the research on screen, align with the findings among older people in Brazilians 34 , 40 and differ from studies conducted in the Netherlands, in which this facet was among those with the worst evaluations. 37 Such data suggest that these individuals are facing, in a good way, concerns and fears related to the end of life, which are items evaluated in this facet.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Grande parte dos idosos não tinha companheiros(as), corroborando com outros estudos que têm apresentado com frequência uma maior ocorrência de idosos viúvos 20,21 . Os idosos entrevistados apresentavam algum grau de escolaridade e tempo médio de institucionalização em torno de um ano.…”
Section: Resultsunclassified

Caracterização da qualidade de vida de idosos institucionalizados

Souza Rosa Brandão,
Lima de Morais Inocêncio,
Da Costa Quintino Júnior
et al. 2023
Anais FMO
“…Tal fenômeno pode ser explicado devido ao Saúde Pública: Princípios e atender as necessidades básicas. Devido às graves distorções na distribuição de renda no país, muitos idosos vivem em extrema pobreza, enquanto outros, para garantir condições mínimas de sobrevivência são obrigados a prolongar sua permanência no mercado de trabalho(SÁ et al, 2011;CUNHA, 2014).…”
unclassified